Kelambanan Reformasi Birokrasi dan Pola Komunikasi Lembaga Pemerintah - Eko Harry Susanto (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2010)
When Indonesia entering the political reform, in the 1998, there’s a strong demand for government to give a better public service. One reason that can support that hope is a bureaucracy reform. But the power shift in the reform era cannot give a good public service as people needed. The most reason is that the communication behavior of the leader in that political situation, trapped in the top down shape. In the mechanic society pattern is difficult to develop a good public services.